Coaches' perception of professional competence as a function of education and experience - Isabel Maria Ribeiro Mesquita; Ana Sofia Figueiredo Marques dos Santos (Universidade Federal de Santa Catarina, 2010)
The aim of this study was to analyze coaches' perception of professional competenceas a function of experience and academic education. The sample consisted of 343 Portuguesecoaches from different sport disciplines. A validated questionnaire was used to collect demographicdata and data regarding the perception of professional competence. Exploratory factorial analysisand comparative inferential analysis by one-way ANOVA were used as statistical procedures. Theresults highlighted the wide range of competences necessary for an efficient coach. The answersprovided by the coaches revealed 5 factors: planning; leadership and coach education; competitionplanning and orientation; personal competence, and training orientation. Although all these factorswere at least classified as reasonably important, factors related to competition were consideredto be the most important. Comparative analysis showed that professional experience and academiceducation had a different impact on the perceived importance of competence. More experiencedcoaches perceived competences related to planning, training orientation, and leadership and coacheducation to be more important than less experienced coaches. Coaches with higher educationconsidered competences related to planning, leadership and coach education, training orientationand personal competence to be more important than undergraduate coaches.